Keragaman Sistem Hukum Pertanahan Lokal Terhadap Pendaftaran Tanah Studi Pelaksanaan PTSL di Ohoi Ngabub dan Ohoi Sathean, Provinsi Maluku - Priska Irvine Loupatty; Julius Sembiring; Ahmad Nashih Luthfi (Tunas Agraria, 2019)
Abstract: Land registration through PTSL activities is conducted for all parcels of land throughout Indonesia. However, there are some ohoi in Southeast Maluku regency that refuse the registration of land which has been implemented through PTSL in recent years, whereas almost all of ohoi in Southeast Maluku Regency has already done land registration. This study aims to determine the implementation of PTSL in Ohoi Ngabub and Ohoi Sathean, the reason the Ohoi Sathean indigenous people accepted PTSL activities and the Ohoi Ngabub indigenous people rejected PTSL activities, and the land law system that applies in both ohoi. The research method used is qualitative with a sociolegal approach. The results showed that PTSL-UKM activities carried out in 2017 at Ohoi Sathean received good responses from the Ohoi Government and indigenous people of Ohoi Sathean, while the Ohoi Ngabub government refused to do PTSL activities. This is due to the local land law system that applies in both ohois. The local land law system that applies in Ohoi Sathean is individual land ownership, whereas the local land law system that applies in Ohoi Ngabub is joint land ownership. Keywords: customary land, communal rights, PTSL, indigenous peoples of Kei Intisari: Pendaftaran tanah melalui kegiatan PTSL dilakukan untuk seluruh bidang tanah di seluruh wilayah Indonesia. Akan tetapi terdapat beberapa ohoi (desa) di Kabupaten Maluku Tenggara yang menolak dilaksanakannya pendaftaran tanah melalui PTSL, sedangkan hampir seluruh ohoi sudah dilakukan pendaftaran tanah. Penelitian ini bertujuan untuk mengetahui pelaksanaan PTSL di Ohoi Ngabub dan Ohoi Sathean, alasan masyarakat adat Ohoi Sathean menerima kegiatan PTSL dan masyarakat adat Ohoi Ngabub menolak kegiatan PTSL, dan sistem hukum pertanahan lokal yang berlaku di kedua ohoi. Metode penelitian yang digunakan yaitu kualitatif dengan pendekatan sosiolegal. Hasil penelitian menunjukan bahwa kegiatan PTSLUKM yang dilaksanakan pada tahun 2017 lalu di Ohoi Sathean mendapatkan tanggapan yang baik dari perangkat ohoi dan masyarakat adat Ohoi Sathean sedangkan perangkat Ohoi Ngabub menolak untuk dilakukan kegiatan PTSL. Hal ini disebabkan oleh sistem hukum pertanahan lokal yang berlaku di kedua ohoi. Sistem hukum pertanahan lokal yang berlaku di Ohoi Sathean yaitu kepemilikan tanah secara individual, sedangkan sistem hukum pertanahan lokal yang berlaku di Ohoi Ngabub yaitu kepemilikan tanah secara bersama. Kata kunci: tanah adat, hak komunal, PTSL, masyarakat adat kei